Pets as family members: Conflicting practices in the use of third-person pronouns to refer to companion animals in written biographical stories in Finnish - Priiki Katri (Estonia, 2025)
In many languages, humans are grammatically distinguished from other animals. In Standard Finnish, different pronouns are used for humans and other animals. The article examines biographical stories, written by nonprofessional Finnish writers, with qualitative and quantitative text analysis and focusing to the shift between these two pronouns in references to pets. In modern societies, companion animals fall between humans and animals in some ways, since people often consider them distinct persons and family members. Although the writers follow Standard Finnish norms in most other aspects, one out of three writers uses personal (human) pronouns to refer to animals. The rest humanise pets in other ways but do not deviate from pronoun norms. The use of personal pronouns in texts is influenced by several factors: the system of colloquial Finnish, the practices of referring to animals in other languages, especially in English, and the changing role of animals in society